CULTURE CLASHES: CAUSES, CONSEQUENCES, AND THEIR SIGNIFICANCE IN MODERN SOCIETY - Hafizoff Sardor,; Mamarajabov Davlatbek, (Ustozlar uchun, 2025)
This article analyzes the causes, consequences, and solutions to cultural clashes that arise in the process of globalization. Using examples from Uzbekistan and other countries, the role of cultural tolerance and communication is highlighted.